Perbandingan Struktur dan Perkembangan Pasar Uang dan Pasar Modal di Indonesia dan Yordania: Studi Pustaka - Melia Sari; Maryam Batubara (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the comparison of the structure and development of money markets and capital markets in Indonesia and Jordan. The research uses a descriptive qualitative approach with a library research method. The data used are secondary data obtained from scholarly literature, official reports, and publications from financial institutions such as Bank Indonesia, the Financial Services Authority, Indonesia Stock Exchange, Central Bank of Jordan, Jordan Securities Commission, Amman Stock Exchange, the World Bank, and the International Monetary Fund. The data were analyzed using content analysis and descriptive-comparative analysis. The findings show that Indonesia has a more complex and developed financial market structure than Jordan. Indonesia’s money market is supported by more diverse instruments, wider institutional participation, and stronger integration with monetary policy. Its capital market is also more advanced, supported by the Financial Services Authority, Indonesia Stock Exchange, KSEI, and KPEI, as well as various investment instruments such as stocks, bonds, sukuk, mutual funds, and ETFs. In contrast, Jordan’s financial market structure is more bank-centered, with a simpler money market and a capital market centered on the Amman Stock Exchange. The differences are influenced by economic size, institutional quality, market depth, financial digitalization, and openness to foreign investment. This study concludes that Indonesia’s money and capital markets are more dynamic and diversified, while Jordan’s markets remain relatively stable but less deep and less liquid.